Pulmonary Empyema with Possible Tuberculosis Infection: A Case Report - Putra, I Gusti Putu Adietha Chandra; Santoso, Resyana; Putra, Wayan Wahyu Semara; Putra, I Wayan Ardyan Sudharta (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Pulmonary empyema is an infectious disease with mortality and morbidity rates ranging between 3% and 33%. It occurs in approximately 8.9% of patients with tuberculosis (TB), and the associated mortality rate is approximately 20%. If not treated promptly following diagnosis, empyema may result in a poor prognosis. Therefore, this case report presented a patient with pulmonary empyema caused by a possible TB infection. Case: A 57-year-old female presented with a two-week history of coughing up yellow phlegm and a three-day history of fever. The patient reported an untreated dental cavity in the right lower tooth for the past three weeks. Physical examination revealed decreased vesicular breath sounds in the right hemithorax’s fifth to sixth intercostal space (ICS). Chest X-ray examination suggested pneumonia and right pleural effusion. Laboratory examinations revealed leukocytosis, thrombocytosis, and an increased neutrophil-to-lymphocyte ratio (NLR). The adenosine deaminase (ADA) level was 89 U/L. Ultrasonography (USG) of the right hemithorax confirmed right pleural effusion. A pleural puncture was performed, and a thoracic drainage was inserted. The procedure yielded approximately 1,700 cc of cloudy brown pus. The patient was diagnosed with right pulmonary empyema caused by tuberculous pleurisy. She received antibiotic therapy and a four-drug fixed-dose combination (FDC) of anti-TB therapy. After nine days of treatment, the patient’s symptoms showed improvement. Conclusion: Empyema is a complex disease with diverse etiologies and multifactorial pathogenesis. Early detection and prompt treatment are essential to minimize the risk of further complications.